Science over stigma : education and advocacy for mental health - Morehead, Daniel B. (American Psychiatric Association Publishing, 2021)
"Recent surveys have found that the vast majority of the public believes that mental illness is real and treatable. And yet, fewer than half of people with diagnosable mental illnesses get treatment in any given year, and of those who do, only half adhere to it. What accounts for the disconnect? According to Daniel Morehead, M.D., unchecked critiques of psychiatry-that it is impossible to define mental illness, that the neurobiology of major mental illnesses is unknown, that patients are overdiagnosed and overmedicated-has led to a public perception that mental health treatment is profoundly flawed. In Science Over Stigma, Dr. Morehead argues that it is time for a full-throated defense of mental health treatment, and that it falls to everyone, from medical and mental health professionals to the general public, to advocate on its behalf. In accessible terms this book sets forth a definition of mental illness, candidly discussing what is known and what remains unknown, and then describes its prevalence, social and physical consequences, and a range of treatments. Each chapter includes advocacy tips that help readerstranslate the information they've learned into the means for constructive dialogue. By clearly laying out the science behind mental illness and its treatment and vividly illustrating how common it is-affecting patients, their friends and family, and mental health professionals themselves-this volume seeks to turn the recognition of psychiatric illness into practical behavior, destigmatizing both the illness itself and the search for treatment"--